IMPLEMENTATION OF BRUTE-FORCE ALGORITHM AND BACKTRACKING ALGORITHM FOR FIREFIGHTING ROBOT SIMULATION - Tegar Arifin Prasetyo; Rudy Chandra; Wesly Mailander Siagian; Tahan HJ Sihombing; Sarbaini Sarbaini (Lambung Mangkurat University, 2023)
In general, a robot is defined as a mechanical device used by humans to ease human work. Robots are usually used for difficult and dangerous tasks. One example of its use is a firefighting robot that replaces human tasks in extinguishing fires. The firefighting robot is on duty to find fire spots in a city then extinguishing them. To be able to put out a fire, the robot must implement an efficient program in finding and determining the shortest path to the location of the fire and then put it out. For this reason, the robot is equipped with proximity and fire sensors to detect the presence of fire. The design is made with a three-step program that is designing needs of robot control, robot control mechanism scheme preparation and implementing an algorithm for making program syntax. The Brute-Force Algorithm can be implemented to indicate the presence of a hotspot signal and the backtracking Algorithm is implemented to find the shortest path to the hotspot location. This paper discusses the use of a brute-force algorithm and a backtracking algorithm in a firefighting robot program to make the fire search process more efficient. The results show that from 8 input fire points, the firefighting robot is able to find all the points within 3.12 seconds with 13 times trial. In its application, the writer used Visual Basic 6.0 in the firefighting robot program.Keywords: Firefighting Robot, Brute-Force Algorithm, and Backtracking Algorithm.Secara umum robot didefinisikan sebagai suatu alat mekanik yang digunakan oleh manusia untuk mempermudah pekerjaan manusia. Robot biasanya digunakan untuk tugas-tugas yang sulit dan berbahaya. Salah satu contoh penggunaannya adalah robot pemadam kebakaran yang menggantikan tugas manusia dalam memadamkan api. Robot pemadam kebakaran bertugas untuk menemukan titik api di suatu kota kemudian memadamkannya. Untuk dapat memadamkan api, robot harus menerapkan program yang efisien dalam mencari dan menentukan jalur terpendek menuju lokasi kebakaran kemudian memadamkannya. Untuk itu, robot dilengkapi dengan proximity dan fire sensor untuk mendeteksi adanya api. Perancangan dibuat dengan tiga langkah program yaitu perancangan kebutuhan pengendalian robot, penyusunan skema mekanisme kendali robot dan implementasi algoritma untuk pembuatan sintaks program. Algoritma Brute-Force dapat diimplementasikan untuk menunjukkan adanya sinyal hotspot dan Algoritma backtracking diimplementasikan untuk mencari jalur terpendek ke lokasi hotspot. Penelitian ini membahas tentang penggunaan algoritma brute force dan algoritma backtracking pada simulasi program robot pemadam kebakaran agar proses pencarian kebakaran menjadi lebih efisien. Hasil penelitian menunjukkan bahwa dari 8 input titik api, robot pemadam kebakaran mampu menemukan semua titik dalam waktu 3,12 detik dengan 13 percobaan. Dalam penerapannya penulis menggunakan Visual Basic 6.0 pada program robot pemadam kebakaran. Kata kunci: Robot Pemadam Kebakaran, Algoritma Brute-Force, dan Backtracking.